Mceliece S Public Key Cryptosystem Based on Non-Binary Algebraic Codes - Soto-Gomez, J; Derpich-Contreras, I (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper we carried out the construction of a public key cryptosystem based on algebraic geometry codes. Basically, we have developed the scheme proposed by McEliece. However, instead of using binary linear codes, we have worked with non-binary linear algebraic geometry codes on Hermitian curves. In the decryption process, we have used Sakata s algorithm, which plays an important role. An application is proposed for this system in order to be applied in a storage and retrieval systems for magnetic recording over nanoparticles. © 2016 IEEE.